ChemInform Abstract: Insecticidal Evaluation and [4 + 2] Aza‐Diels—Alder Synthesis of 3, 7‐Diaryl‐6, 7‐dihydro‐5H‐6‐substituted Thiazolo[3, 2‐a]pyrimidin‐5‐ones under Coupled Ultrasonic Irradiation and PTC. Issue 23 (May 2016) - Gupta, Ragini; Sharma, Deepti; Verma, P. S.; Jain, Anshu
Abstract: The title compounds are prepared by [4+2] cycloaddition reaction of thiazole Schiff′s bases and in situ generated monosubstituted ketenes under phase transfer catalysis (PTC) conditions coupled with ultrasonication.